IMPROVING STUDENT COMPETENCY IN MAIL MANAGEMENT THROUGH ROLE PLAYING LEARNING METHOD IN A RECORDS MANAGEMENT COURSE - Ika Rachmawati; Hindra Kurniawan (Sean Institute, 2023)
This study aims to determine the implementation of role-playing learning methods to improve students' ability in mail management in archives management courses. The mechanism used in this study is classroom action research with the Kemmis & Taggart model. Data collection has assisted through pre-test, post-test, observation, and interview. The study was conducted in two stages, known as Cycle I and Cycle II. Planning, acting, observing outcomes, and reflecting are the four tasks that make up each cycle. The outcome of this study shows that the adoption of role-playing methods can improve students' understanding and ability in letter management. The pre-test and post-test outcomes show a very significant increase in student competence. Additionally, the defined learning objectives can be completed. Students find role-playing techniques to be more captivating, which enhances engagement and learning effectiveness.